2005
DOI: 10.1016/j.eupc.2005.02.118
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Fatty acids and ventricular arrhythmias in patients with ischaemic heart disease and implantable cardioverter defibrillators

Abstract: Patients with a low content of n-3 PUFA in serum had a higher incidence of ventricular arrhythmias compared with patients with high serum levels of n-3 PUFA. The data suggest that the protection offered by n-3 PUFA against sudden cardiac death observed in previous studies is mediated by a direct antiarrhythmic effect of n-3 PUFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…For three of the ten patients, VT could not be induced even at baseline and, interestingly, these patients had a higher mean plasma phospholipid omega-3 FA content than those with inducible arrhythmia (6.2% vs 4.8%). The same inverse relationship between FA content and incidence of malignant ventricular arrhythmias was demonstrated by Christensen et al [21] in 98 patients with ischemic heart disease and implantable cardioverter defibrillators (ICDs). During 1-year follow-up, those with the lowest level of omega-3 FAs in serum phospholipids (mean, 5.5%) had more ventricular arrhythmias than those with the highest concentrations (mean, 13.0%).…”
Section: Human Evidence For An Anti-arrhythmic Effect Of Omega-3 Fassupporting
confidence: 54%
“…For three of the ten patients, VT could not be induced even at baseline and, interestingly, these patients had a higher mean plasma phospholipid omega-3 FA content than those with inducible arrhythmia (6.2% vs 4.8%). The same inverse relationship between FA content and incidence of malignant ventricular arrhythmias was demonstrated by Christensen et al [21] in 98 patients with ischemic heart disease and implantable cardioverter defibrillators (ICDs). During 1-year follow-up, those with the lowest level of omega-3 FAs in serum phospholipids (mean, 5.5%) had more ventricular arrhythmias than those with the highest concentrations (mean, 13.0%).…”
Section: Human Evidence For An Anti-arrhythmic Effect Of Omega-3 Fassupporting
confidence: 54%
“…n-3 PUFAs have been associated with decreased risk of ventricular arrhythmias (4,5) and sudden cardiac death (SCD) (6). Some authors have suggested that the beneficial impact on SCD could be mediated by enhancing the heart rate variability (HRV), which represents the sympathetic and parasympathetic activities of the autonomic nervous system (ANS).…”
Section: Introductionmentioning
confidence: 99%
“…In an observational study by Christensen et al, 98 patients with CAD who had ICDs gave blood for analysis of n-3 PUFA concentrations, and the prevalence of appropriate ICD therapy in the preceding 12 months was analyzed. 80 Investigators found that patients with multiple VT/VF events had lower n-3 PUFA levels than patients with no events (mean 7.1% vs. 9.2%, P Ͻ 0.01). Those in the lowest quintiles of n-3 PUFA levels had significantly more VT/VF events than those in the highest quintile (mean 1.3 events vs. 0.2 events, P Ͻ 0.05).…”
Section: Effect Of N-3 Pufas In Patients With Implantable Cardiovertementioning
confidence: 93%